2021
DOI: 10.3390/s21175751
|View full text |Cite
|
Sign up to set email alerts
|

Functional Living Skills: A Non-Immersive Virtual Reality Training for Individuals with Major Neurocognitive Disorders

Abstract: The loss of functional living skills (FLS) is an essential feature of major neurocognitive disorders (M-NCD); virtual reality training (VRT) offers many possibilities for improving FLS in people with M-NCD. The aim of our study was to verify the effectiveness of a non-immersive VRT on FLS for patients with M-NCD. VRT was carried out for 10 to 20 sessions, by means of four 3D apps developed in our institute and installed on a large touch screen. The experimental group (EG) and the control group (CG) included 24… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(35 citation statements)
references
References 43 publications
(62 reference statements)
2
26
0
Order By: Relevance
“…In terms of patient satisfaction, the feedback from patients on their experience of VR training was consistent with that collected in other studies on the use of non-immersive VR for the learning of functional living skills (Panerai et al 2021 ). Perception of satisfaction is defined as one of the effective outcomes of learning experience in education and training (Sharda et al 2004 ).…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…In terms of patient satisfaction, the feedback from patients on their experience of VR training was consistent with that collected in other studies on the use of non-immersive VR for the learning of functional living skills (Panerai et al 2021 ). Perception of satisfaction is defined as one of the effective outcomes of learning experience in education and training (Sharda et al 2004 ).…”
Section: Discussionsupporting
confidence: 79%
“…This shows that VR training is an effective method of procedural learning for use as an adjunct to conventional PD exchange education, particularly for ERSD patients with cognitive deficits. The non-immersive VR applied in this study provided a type of interactive experience, based on “learning-by-doing,” the efficacy of which is supported in the findings of previous studies (Panerai et al 2021 ; Dalgarno and Lee 2010 ). Training within a virtual environment that explicitly displays the PD exchange process allows patients to see themselves completing the task, which in turn better enables them to problem solve their way out of difficulties and gradually improve their method.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…The study results indicated that the hybrid group had generally higher perceived presence and lower cognitive load than the control and real tool groups. These results (1) demonstrate that increasing realism by having more realistic devices does not always lead to greater user experience and (2) highlight the strategic use of real tools in combination with standard VR controllers to optimize user experience and achieve training goals.…”
Section: Introductionmentioning
confidence: 93%
“…Virtual reality (VR) has gained much attention as a technology that is suitable for training services in many domains because it provides trainees with realistic experiences and methods for coping with various situations [1][2][3][4][5][6]. VR has not only significantly lowered cost and space requirements compared to a real training environment but has also allowed trainees to conduct repetitive training at any time without material and environmental restrictions, further increasing its impact, educational value, and a trainee's self-efficacy.…”
Section: Introductionmentioning
confidence: 99%